Once More. . (2001)
Black, Matthew (ed.), Peake’s Commentary on the Bible Mills, Watson E. and Wilson, Richard F. (eds), Mercer Commentary on the Bible. Volume 3: (Wisdom) Writings Barrett, David B., Kurian, George T. and Johnson, Todd M., World Christian Encyclopedia: A Comparative Survey of Churches and Religions in the Modern World (Second Edition, 2 vols) Dupré, Louis Symbols of the Sacred